PENGUATAN KOMPETENSI SANTRI MELALUI PENDIDIKAN KEWIRAUSAHAAN DI MA TAHFIZUL QUR’AN ISTIQOMAH SAMBAS PURBALINGGA - Noegroho, Asharryadi; Triwibowo, Rony Nur (Aspirasi Masyarakat, 2025)
The community service program, especially for students at the Tahfizul Qur'an Istiqomah Islamic High School in Sambas, Purbalingga, aims to empower students by improving their competence and fostering an entrepreneurial mindset. This community service team consists of the academic community of the Faculty of Economics and Business, Al-Irsyad University Cilacap. Empowering santri with entrepreneurial acumen not only changes their future, but also the vitality of their community. Interactive workshops, mentoring programs, and real-world business projects equip them with critical thinking skills, creativity, and a resilient mindset. This blend of spiritual learning and practical business skills fosters well-rounded individuals who are ready to navigate and contribute to the modern economic landscape. This initiative not only teaches them how to start a business, but also fosters confidence. This approach echoes the transformative impact seen when the education system integrates practical skills—such as how the incorporation of technology in the classroom has changed the learning experience globally. Expanding such entrepreneurship programs can unlock untapped potential in other educational institutions, empowering more generations of young people to become catalysts for change in their own communities. Evaluation results show significant improvements in critical thinking, problem solving, and creativity. The program encourages students to think creatively and develop innovative solutions and business ideas. Students are better prepared to contribute to the economic development of their community, either by starting their own business or contributing to an existing business.